Gel polymer electrolyte based on N-Phthaloyl chitosan and its application in DYE-Sensitized solar cells / Siti Nor Farhana Yusuf - Siti Nor Farhana , Yusuf (2017)
It is widely known that chitosan is not soluble in common organic solvents. Hence there is a need to increase its solubility in a wider range of solvents. To do this, the chitosan biopolymer has been modified by the process of phthaloylation to form N-phthaloyl chitosan (PhCh) by reacting phthalic anhydride with chitosan in dimethylformamide (DMF). The chitosan derivatives, PhCh, can dissolve in DMF, DMSO, DMAc and pyridine. Fourier transform infra-red (FTIR) and proton nuclear magnetic resonance (1H NMR) spectroscopies were used to confirm the PhCh formation and structure. The phthalimido and aromatic peaks of PhCh were seen at 1772, 1708 and 719 cm−1, respectively, and two sets of peaks from 1H NMR centered at 3.0 and 7.5 ppm verified that chitosan has been phthaloylated. The PhCh-based gel polymer electrolytes (GPE) consist of ethylene carbonate (EC), and DMF with different contents of tetrapropylammonium iodide (TPAI) and iodine. X-ray diffraction studies reveal that addition of tetrapropylammonium iodide (TPAI) further reduced the crystallinity of the PhCh. FTIR spectroscopy showed the interaction between polymer, plasticizer and salt. GPE comprising of PhCh : EC : DMF : TPAI : I2 in wt.% ratio of 12.0 : 36.1 : 36.1 : 14.4 : 1.4 exhibited the highest conductivity of 5.46 mS cm−1 at 30 ℃. When used in dye-sensitized solar cell (DSSC), it gave the best performance with the efficiency of 5.0 %, JSC of 12.72 mA cm−2, VOC of 0.60 V and fill factor of 0.66. To further improve the efficiency of the solar cell, lithium iodide (LiI) has been added to the PhCh-based electrolyte. The efficiency improved to 6.36 %, with the JSC of 17.29 mA cm‾2, VOC of 0.59 V and fill factor of 0.62. Addition of 1-butyl-3-methylimidazolium iodide (BMII) ionic liquid to the electrolyte enhanced the DSSC efficiency to 6.69 % with the JSC of 16.53 mA cm‾2, VOC of 0.62 V and fill factor of 0.65.